Doxing untuk Malicious Purposes vs Doxing untuk Political Purposes: Urgensi Pengklasifikasian Ancaman Hukuman Bagi Para Pelaku Doxing dalam Undang-Undang Nomor 27 Tahun 2022 tentang Perlindungan Data Pribadi - Nafila Andriana Putri (Padjadjaran Law Review, 2023)
Along with the massive use of social media by Indonesians, cases of doxing using social media are also common. The purpose of doxing varies from wanting to humiliate someone to seeking justice in the public interest. The enactment of Law No. 27 of 2022 on Personal Data Protection (PDP Law) is expected to provide reliable regulations related to personal data issues, but in fact, the PDP Law has not been able to provide legal certainty, especially for doxing actors to demand justice in the public interest. UU PDP generalizes that the activity of disclosing personal data or doxing is prohibited and punishable by criminal law. By using the normative juridical research method and a case study of doxing in the Mario Dandy (MDS) persecution case against D, this paper will discuss the importance of classifying doxing based on its form and purpose in the PDP Law. The results of this study show that doxing consists of three categories based on its purpose, which is doxing for malicious purpose, doxing for political purpose, and doxing for self-regulation doxing. Based on this categorization, it is necessary to differentiate the punishment for doxing actors.